High-oxygen-permeability silicone hydrogel contact lens and preparation method thereof

By optimizing the reaction conditions and post-treatment steps of macromolecular siloxane I, the introduction of quaternary ammonium salt functional groups was solved, and the problem of insufficient hydrophilicity and wetting of the surface of silicon hydrogel contact lens lenses was achieved, and high oxygen permeability, anti-protein adsorption and excellent wearing comfort were achieved.

CN119638919AActive Publication Date: 2025-03-18SHANGHAI DILUO MEDICAL EQUIPMENT CO LTD +1

Patent Information

Application Number
CN202411838048.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-18
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

The existing silicon hydrogel contact lenses have shortcomings in the hydrophilicity and wetting properties of the lens surface, which leads to uncomfortable wearing and further improvement in the anti-protein adsorption performance.

Method used

By optimizing the reaction conditions and post-treatment steps of macromolecular siloxane I, it ensures that its molecular weight distribution coefficient is less than 1.8, and quaternary ammonium salt functional groups are introduced into the molecule to improve the uniformity of macromolecular siloxane in the PP mold, thereby improving the hydrophilic surface of the lens.

Benefits of technology

The lens has high oxygen permeability, excellent high humidity surface and anti-protein adsorption properties, and excellent wearing comfort without surface treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638919A_ABST
    Figure CN119638919A_ABST
Patent Text Reader

Abstract

The invention discloses high-oxygen-permeability silicone hydrogel contact lenses, which are prepared from the following raw material components in percentage by mass: 30 to 40 percent of macromolecular siloxane I, 5 to 10 percent of macromolecular siloxane II, 10 to 20 percent of micromolecular siloxane, 20 to 30 percent of hydrophilic monomers, 2 to 5 percent of humectants, 0.5 to 1.5 percent of cross-linking agents, 0.5 to 1 percent of initiators and 2 to 5 percent of functional monomers. The macromolecular siloxane I adopted by the silicone hydrogel contact lens is narrow in molecular weight distribution and good in reaction repeatability, a quaternary ammonium salt functional group is introduced into the macromolecular siloxane I, uniformity of the macromolecular siloxane in a PP mold is facilitated, and the lens has a better hydrophilic surface; meanwhile, preparation process equipment of the macromolecular siloxane I is simple, raw materials are cheap and easy to obtain, and operation is convenient; the obtained lens is high in oxygen permeation coefficient, and the lens with good surface hydrophilicity and good wetness can be obtained without surface treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of contact lens preparation, and in particular to a high oxygen permeable silicone hydrogel contact lens and a preparation method thereof. Background Art

[0002] The usage rate of silicone hydrogel contact lenses has far exceeded that of traditional hydrogel contact lenses. This is because the high oxygen permeability of silicone hydrogel allows the wearer to wear comfortably for a longer period of time. The introduction of fluorine into silicone hydrogel contact lenses can further improve the oxygen permeability of contact lenses, while also making the lenses have better processing performance and better improving the shortcomings of silicone hydrogel lenses in resisting protein adsorption. However, polydimethylsiloxane will make the lens surface non-hydrophilic, and low wettability will cause discomfort to the wearer, which requires the introduction of hydrophilic groups from the molecular structure.

[0003] Patent CN 101163991A discloses a method for preparing macromolecular silicone containing allyl polyethylene glycol ether similar to fluorosilicone, but it is also necessary to cooperate with a modified PP mold (increasing the polarity of the mold) to prepare silicone hydrogel lenses, because the conventional PP mold surface polarity is small, so that the silicon component in the polymer solution is enriched on the PP mold surface, resulting in insufficient wettability of the lens surface. CN101589091A discloses the preparation of macromolecular siloxane containing quaternary ammonium salt, but the preparation method needs to be optimized. More methods to improve the wettability of the lens surface are: lens surface treatment (such as: CN 104837612A; CN 107532083A), adding moisturizers such as PVP. Summary of the invention

[0004] The present invention aims at the deficiencies in the prior art and provides a high oxygen permeability silicone hydrogel contact lens and a preparation method thereof. The reaction conditions of macromolecular siloxane I are optimized and low molecular weight polymers are removed through more optimal post-treatment conditions, thereby ensuring that the molecular weight distribution coefficient of the macromolecular siloxane I is less than 1.8; at the same time, a quaternary ammonium salt functional group is introduced into the molecule, which is beneficial to the uniformity of the macromolecular siloxane in a PP mold, so that the lens obtains a better hydrophilic surface, greatly improves the initial wearing feeling of the prepared lens, and at the same time, the antibacterial property of the quaternary ammonium salt better protects the eye health of the wearer; in addition, the lens of the present invention has high oxygen permeability, and also has the advantages of excellent high wettability surface, anti-protein adsorption, and no need for surface treatment.

[0005] In order to solve the above technical problems, the first aspect of the present invention provides a highly oxygen permeable silicone hydrogel contact lens, comprising the following raw material components: macromolecular siloxane I, macromolecular siloxane II, small molecule siloxane, hydrophilic monomer, humectant, crosslinking agent, initiator and functional monomer;

[0006] The molecular weight of the macromolecular siloxane I is 10000-15000, the molecular weight distribution coefficient is less than 1.8, and the structural formula is:

[0007]

[0008] Wherein, a:b:c=(0.1-0.2):0.1:(0.7-0.8); b / (a+c)=1 / 9, d is 7-8 or 23-30;

[0009] The structural formula of the macromolecular siloxane II is:

[0010]

[0011] Wherein, R1 is H or CH3, R2 is one of C3-C6 alkyl groups, and n is a natural number between 9 and 24;

[0012] The structural formula of the moisturizing agent is:

[0013]

[0014] Wherein, R is one of H, OH, and polyhydroxy compounds; X and Y are independently one of O, S, and N, and the anion can also be bromine, iodine, or other organic acid groups.

[0015] Furthermore, the preparation method of the macromolecular siloxane I comprises the following steps:

[0016] S1. Add 1,3-bis(3-chloropropyl)tetramethyldisilane, D3F, D3, D3H and phosphonium alkoxide to an organic solvent, add trifluoromethanesulfonic acid at low temperature and stir for 2 hours, then slowly heat up and react for 22-24 hours, and post-treat to obtain intermediate I;

[0017] S2, the intermediate I and allyl polyethylene glycol ether are subjected to addition reaction in an organic solvent, and post-processed to obtain intermediate II;

[0018] Wherein, Karstedt catalyst or Speier catalyst is added before the addition reaction, and the addition reaction temperature is 25-50°C;

[0019] S3, the intermediate II and N-(3-dimethylaminopropyl)methacrylamide are heated to reflux reaction in an organic solvent, and then post-treated and freeze-dried to obtain the macromolecular siloxane I;

[0020] The structural formulas of D3F, D3, D3H, phosphonium alkoxide, intermediate I and intermediate II are respectively:

[0021]

[0022]

[0023] Among them, a:b:c=(0.1-0.2):0.1:(0.7-0.8); b / (a+c)=1 / 9, and d is 7 or 8.

[0024] In S1, the three raw materials D3F, D3, and D3H used for the ring-opening reaction are all six-membered rings containing three silicon atoms, so as to obtain similar ring-opening reaction rates.

[0025] Furthermore, in S1, the organic solvent is one of toluene, dichloromethane, chloroform, and tetrahydrofuran, or a mixture of two of them.

[0026] Furthermore, in S2, the organic solvent is one or a mixture of two of isopropanol, methanol, ethanol, acetonitrile and toluene.

[0027] Furthermore, in S3, the organic solvent is one of isopropanol, methanol, ethanol, and acetonitrile, or a mixture of two of them.

[0028] Furthermore, in S1, the temperature for adding trifluoromethanesulfonic acid is 0°C, and the reaction temperature is 10°C. The lower reaction temperature is for better control of the molecular weight distribution, and the ring opening of D3 can be well carried out at low temperature;

[0029] The organic solvent accounts for 80% of the total reaction volume, and the low reaction concentration can better inhibit the generation of ultra-large molecular polymerization products;

[0030] The post-treatment is specifically as follows: using a mixed solvent of methanol and nitromethane in a volume ratio of 5:1 to extract oligomers and a small amount of un-ringed raw materials and other cyclic by-products generated in the reaction.

[0031] Furthermore, in S2, the post-treatment is specifically as follows: dissolving the crude intermediate II in a mixed solvent of methyl tert-butyl ether and ethyl acetate in a volume ratio of 1:5, and then extracting the remaining raw material allyl polyethylene glycol ether with purified water.

[0032] Furthermore, in S3, the post-treatment is specifically as follows: dissolving the crude macromolecular siloxane I in purified water, and then extracting the remaining raw material N-(3-dimethylaminopropyl) methacrylamide with a mixed solvent of dichloromethane and ethyl acetate in a volume ratio of 1:1.

[0033] Furthermore, in S3, the water content of the freeze-dried product is less than 0.15 wt%.

[0034] Furthermore, the composition includes the following components by mass percentage: 30-40% macromolecular siloxane I, 5-10% macromolecular siloxane II, 10-20% small molecular siloxane, 20-30% hydrophilic monomer, 2-5% moisturizing agent, 0.5-1.5% crosslinking agent, 0.5%-1% initiator and 2-5% functional monomer.

[0035] Further, the small molecule siloxane is methacryloxypropyl tris(trimethylsiloxy)silane and / or (3-methacryloxy-2-hydroxypropoxy)propyl bis(trimethylsiloxy)methyl;

[0036] And / or, the hydrophilic monomer is one or more of N-vinyl pyrrolidone, N,N-dimethylacrylamide, N-methyl-N-vinylacetamide, and N-vinylacetamide;

[0037] And / or, the cross-linking agent is ethylene glycol dimethacrylate and / or tetraethylene glycol dimethacrylate;

[0038] And / or, the initiator is azobisisobutyronitrile (AIBN);

[0039] And / or, the functional monomer includes one or more of a UV absorber, a molecular weight regulator, a lens morphology improver, a demoulding accelerator, and a reactive dye.

[0040] Furthermore, the ultraviolet absorber is one or more of UV416, UV090, and UV725; the molecular weight regulator is allyl hydroxyethyl ether; the lens morphology improver is one or more of 2-hydroxyethyl methacrylate, glycidyl methacrylate, isobornyl methacrylate, and methyl methacrylate; the demolding promoter is sodium salt of bis(2-ethylhexyl)sulfosuccinate; and the reactive dyes are RB246 and / or RB247.

[0041] The second aspect of the present invention provides a method for preparing the highly oxygen permeable silicone hydrogel contact lens described in the first aspect, characterized in that the raw material components are mixed and dissolved in an organic solvent to obtain a polymer solution, the polymer solution is placed in a mold under a protective atmosphere of nitrogen for heat treatment, and the mold is demolded and extracted after natural cooling to room temperature to obtain the highly oxygen permeable silicone hydrogel contact lens.

[0042] Furthermore, the heat treatment is specifically as follows: keeping the temperature at 60°C for 60-100 minutes, then increasing the temperature uniformly to 110-120°C for 4 hours, and keeping the temperature for 1 hour.

[0043] Furthermore, the demoulding and extraction are specifically to place the heat-treated mold in a 20wt%-80wt% ethanol aqueous solution for hydration, so as to demould the lens and extract a small amount of residual monomers and oligomers in the lens.

[0044] Beneficial effects of the present invention:

[0045] The macromolecular siloxane I used in the silicone hydrogel contact lens of the present invention has a narrow molecular weight distribution and good reaction repeatability, and the introduction of a quaternary ammonium salt functional group is beneficial to the uniformity of the macromolecular siloxane in a PP mold, so that the lens obtains a better hydrophilic surface; at the same time, the preparation process equipment of the macromolecular siloxane I is simple, the raw materials are cheap and easily available, and the operation is convenient.

[0046] The lens of the present invention has a high oxygen permeability coefficient and excellent resistance to protein adsorption. At the same time, no solvent needs to be introduced into the polymerization liquid, and a lens with good surface wetting can be obtained without surface treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] In order to more clearly illustrate the technical solution of the present invention, the drawings required for use in the embodiments are briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0048] Figure 1 This is the nuclear magnetic spectrum of the macromolecular siloxane I prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0049] The technical solution of the present invention will be described clearly and completely below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0050] Example 1

[0051] This embodiment relates to a method for preparing macromolecular siloxane I, comprising the following steps:

[0052] S1. Add 5000mL chloroform (water content less than 100ppm) to a 10L jacketed reactor, and then add 40g 1,3-bis(3-chloropropyl)tetramethyldisilane, 550g D3, 116g D3F, 55g D3H, and 1.5g phosphonium alkoxide. Turn on stirring, cool the reaction solution to 0°C under nitrogen protection, add 0.3g trifluoromethanesulfonic acid with a syringe, keep stirring at 0°C for 2 hours, turn on the high and low temperature circulation device, maintain the liquid temperature at 10°C, and continue to keep warm for 22 hours. Add 2g powdered sodium bicarbonate, continue stirring for 3h, neutralize trifluoromethanesulfonic acid, and quench the reaction. Filter, concentrate the filtrate to remove the solvent, and obtain 0.77kg crude product. Add 230ml mixed solvent (methanol: nitromethane = 5:1) for washing and let stand for stratification. The lower layer is a slightly milky white liquid, which is the product phase, and the upper layer is a clear liquid (containing small molecular oligomers). Repeat the washing three times. After removing the light components from the lower target phase, 500g of product intermediate I is obtained, which is a colorless and clear liquid. The designed molecular weight is about 5300. 1 HNMR showed that the actual molecular weight was 6300. GPC detection of intermediate I was performed under the following conditions: (1) Equipment: LC-20ADXR pump; RID-20A differential refractometer; LabSulutions chromatography workstation; CTO-20A chromatographic column thermostat; SIL-20AXR autosampler. (2) Method: Standard: PEG / PEO (molecular weight 3140-250000); Mobile phase: acetonitrile: water = 75:25; Chromatographic column: SB-804HQ 300*8.0mm 10um; Flow rate: 0.8ml / min.; Column temperature: 40℃; Detector temperature: 40℃; Time: 20min. GPC detection results showed a distribution coefficient of 1.4.

[0053] S2. Add 1.2L isopropanol to a 5L reaction bottle, and then add 500g of intermediate I and 338g of allyl polyethylene glycol ether (molecular weight 400-450). Start stirring, maintain the reaction solution at 25°C under nitrogen protection, add 0.8g of Karstedt catalyst (platinum (0)-1,3-diethylene-1,1,3,3-tetramethyldisiloxane complex solution, platinum 2%) with a syringe, and keep stirring at 25 degrees for 12 hours. During the reaction, the system changes from a slightly milky white turbid liquid to a light yellow clear transparent liquid. After reducing pressure and concentrating to remove the solvent, a viscous, almost solid liquid is obtained. Add 1600ml of a mixed solvent of methyl tert-butyl ether: ethyl acetate = 1:5, stir and dissolve, then add 300ml of purified water for washing, let stand and separate, the upper layer is a slightly yellow transparent liquid as the target phase, the lower layer is the aqueous phase, and the organic phase is washed with water 3 times to wash away excess raw material allyl polyethylene glycol ether and other impurities. The organic phase was concentrated to remove the solvent to obtain the target product intermediate II, a light yellow transparent liquid of 780 g. 1HNMR showed a molecular weight of about 9300.

[0054] S3. Add 1.0L ethanol to a 5L reaction bottle, then add 780g of intermediate II and 31g of N-(3-dimethylaminopropyl)methacrylamide. Heat to 80℃ for 12h, add 50g of activated carbon (for decolorization), continue heating for half an hour, filter while hot, and concentrate the filtrate to remove ethanol. Add 2L of purified water to the residue, stir to dissolve, add 160ml of mixed solvent (dichloromethane: ethyl acetate = 1:1) and wash 3 times until the excess N-(3-dimethylaminopropyl)methacrylamide raw material is completely washed. The aqueous phase containing the product is filtered again through a G6 sand core funnel and freeze-dried to obtain the product, which is a slightly yellow viscous liquid product of 675g. The nuclear magnetic resonance of the product (solvent: deuterated chloroform) is as follows Figure 1 As shown, it can be seen that the molecular weight is about 10,000.

[0055] Example 2

[0056] This embodiment relates to a method for preparing macromolecular siloxane I, comprising the following steps:

[0057] S1. Add 13000mL toluene (water content less than 100ppm) to a 20L jacketed reactor, and then add 60g 1,3-bis(3-chloropropyl)tetramethyldisilane, 1100g D3, 420g D3F, 118g D3H, and 2.1g phosphonium alkoxide. Turn on stirring, reduce the reaction solution to 0℃ under nitrogen protection, add 0.9g trifluoromethanesulfonic acid with a syringe, keep stirring at 0℃ for 2 hours, turn on the high and low temperature circulation device, maintain the liquid temperature at 10℃, and continue to keep warm for 22 hours. Add 4g powdered sodium bicarbonate, continue stirring for 3h, neutralize trifluoromethanesulfonic acid, and quench the reaction. Filter, concentrate the filtrate to remove the solvent, and obtain 1.69kg crude product. Add 500ml mixed solvent (methanol: nitromethane = 5:1) for washing and let stand for stratification. The lower layer is a slightly milky white liquid, which is the product phase, and the upper layer is a clear liquid (containing small molecular oligomers). Repeat the washing three times. After removing the light components from the lower target phase, 1080g of product intermediate I is obtained, which is a colorless and clear liquid. The designed molecular weight is about 8200, 1 HNMR showed that the actual molecular weight was 9800. GPC detection (conditions were the same as in Example 1) molecular weight distribution coefficient: 1.38.

[0058] S2, add 3.0L acetonitrile to a 5L reaction bottle, add 1080g of intermediate I, 670g of allyl polyethylene glycol ether (molecular weight 1000) in sequence, and heat. Turn on the stirring, wait for the allyl polyethylene glycol ether to dissolve, under nitrogen protection, add 2.5g of Speier catalyst (isopropanol solution of chloroplatinic acid, 1g of chloroplatinic acid dissolved in 50ml of isopropanol) with a syringe, keep stirring at 50℃ for 16 hours. During the reaction, the system changes from a milky white turbid liquid to a light yellowish brown clear transparent liquid. After the solvent is removed by vacuum concentration, a viscous nearly solid liquid is obtained, 6000ml of a mixed solvent of methyl tert-butyl ether: ethyl acetate = 1:5 is added, and after stirring and dissolving, 500ml of purified water is added for washing, and the upper layer is a slightly yellow transparent liquid as the target phase, and the lower layer is the aqueous phase. The organic phase is repeatedly washed with water 3 times (the stratification is particularly slow and needs to be left to stand for a long time), and the excess raw material allyl polyethylene glycol ether is washed. The organic phase was concentrated to remove the solvent to obtain the target product intermediate II, a slightly yellow waxy solid: 1465 g, 1 HNMR showed a molecular weight of about 12700, and GPC test results (same conditions as above) showed a molecular weight distribution coefficient of 1.52.

[0059] S3, add 2.5L acetonitrile to a 5L reaction bottle, then add 1465g of intermediate II and 45g of N-(3-dimethylaminopropyl)methacrylamide. Heat to 80°C for 12 hours, add 50g of activated carbon (for decolorization), continue heating for half an hour, filter while hot, and concentrate the filtrate to remove acetonitrile. Add 3L of purified water to the residue, stir to dissolve, add 300ml (dichloromethane: ethyl acetate = 1:1) and wash 3 times until the excess N-(3-dimethylaminopropyl)methacrylamide raw material is completely washed. The aqueous phase containing the product is filtered again through a G6 sand core funnel and freeze-dried to obtain the product, which is a slightly yellow solid product of 1322g, 1 HNMR showed a molecular weight of about 13100. GPC test results (same conditions as above) showed a molecular weight distribution coefficient of 1.46.

[0060] Embodiment 3-9

[0061] This embodiment relates to a method for preparing a silicone hydrogel contact lens, which specifically comprises the following steps:

[0062] In a 5000mL single-necked bottle with stirring, the following compounds (replaced by A, B, C...W) are selectively added. There is no special requirement for the order of addition. The raw material components added in each example are shown in Table 1 by weight.

[0063] A: Siloxane I obtained in Example 1 (α,ω-bis(methacryloxypropyl)-poly(dimethylsiloxane)-poly(trifluoropropyl-methylsiloxane)-poly(ω-methoxy-poly(ethylene glycol)propylmethylsiloxane)), molecular weight: 10,000.

[0064] B: Siloxane I obtained in Example 2, molecular weight: 13100.

[0065] C: Macrosiloxane II: [Methacryloxy (3-dimethylsilyl)propyl]-terminated n-propyl-terminated polymethyl-trifluoropropyl-siloxane (CAS: 1072465-05-3).

[0066] D: Hydrophilic monomer 1: N-vinylacetamide (CAS: 5202-78-8).

[0067] E: Hydrophilic monomer 2: N-vinyl pyrrolidone (CAS: 88-12-0).

[0068] F: Hydrophilic monomer 3: N,N-dimethylacrylamide (CAS: 2680-03-7).

[0069] G: Hydrophilic monomer 4: N-methyl-N-vinylacetamide (CAS: 3195-78-6).

[0070] H: small molecule siloxane 1: methacryloxypropyl tris(trimethylsiloxy)silane (CAS: 17096-07-0).

[0071] I: Small molecule siloxane 2: (3-methacryloyloxy-2-hydroxypropoxy)propyl bis(trimethylsilyloxy)methyl (CAS: 69861-02-5)

[0072] J: Moisturizer 1 Structural formula: Wherein R=OH, X, Y are oxygen).

[0073] K: The structural formula of moisturizer 2 is the same as that of moisturizer 1, wherein R=H, X, and Y are nitrogen.

[0074] L: Cross-linking agent 1: ethylene glycol dimethacrylate (CAS: 97-90-5).

[0075] M: Crosslinking agent 2: tetraethylene glycol dimethacrylate (CAS: 45103-58-0).

[0076] N: UV absorber 1: 2-(4-benzoyl-3-hydroxyphenoxy)ethyl 2-acrylate (UV416, CAS: 16432-81-8).

[0077] O: UV absorber 2: 2-[3-(2H-benzotriazol-2-yl)-4-hydroxyphenyl]ethyl 2-methacrylate (UV090, CAS: 96478-09-0).

[0078] P: 2-Hydroxyethyl methacrylate (CAS: 868-77-9).

[0079] Q: Glycidyl methacrylate (CAS: 106-91-2).

[0080] R: Methyl methacrylate (CAS: 7534-94-3).

[0081] S: isobornyl methacrylate (CAS: 106-91-2).

[0082] T: bis(2-ethylhexyl)sulfosuccinate sodium salt (CAS: 577-11-7).

[0083] U: Reactive dye 1: RB246 (CAS: 121888-69-5).

[0084] V: Reactive dye 2: RB247 (CAS: 109561-07-1).

[0085] W: allyl hydroxyethyl ether (CAS: 111-45-5).

[0086] In addition to the above substances, 10% of the total mass of isopropanol is added, and the materials are stirred at 20-25°C to dissolve all the materials and mix them evenly. The stirring time is 1 hour. The obtained mixed solution is filtered through a filter press with a pore size of 0.2 microns to obtain a formula polymer solution. It is added to the full mold (material: the female mold is PP, the male mold is PP, and the PP material does not need to be modified to enhance the polarity) through an automatic liquid injection machine and put into an oven for curing. The heating program is: the room temperature is raised to 60 degrees and kept warm for 60 minutes, then the temperature is raised to 110 degrees at a uniform speed for 4 hours, kept warm for 1 hour, and then the temperature is lowered to 40 degrees at a uniform speed for 4 hours, and then removed from the oven to obtain the lens to be demolded.

[0087] Use a mold separator to separate the negative mold and directly absorb the dry film. The dry film is first swollen with a 20% ethanol aqueous solution. Then replace the 20% ethanol aqueous solution with an 80% ethanol aqueous solution and soak for 1 hour. The amount of lens and solvent is: 2ml 80% ethanol aqueous solution for 1 lens. After the extraction is completed, add pure water for balancing three times (each time for 0.5h), 3ml purified water for 1 lens, and finally physiological saline for balancing for 1h, and sterilize to obtain the lens. The sterilization conditions are high-pressure steam sterilization, temperature 120 degrees, 25 minutes.

[0088]

[0089]

[0090] The lenses obtained in Examples 3-9 were tested:

[0091] ADk test:

[0092] The oxygen permeability was measured by polarography using a 201T oxygen permeability meter (Creathch / Rehder-Dev Co, USA) according to the national standard GBT 11417.7-2012. The results are shown in Table 2. The unit of Dk in this article is: 10 -11 (cm 2 / s)[mLO2 / (mL.hPa)].

[0093] B. Ultraviolet transmittance detection:

[0094] The transmittance was tested using an SP-1920 UV spectrophotometer (manufactured by Shanghai Spectrum), and the transmittance of the lens was scanned according to GBT11417.5-2012. In this case, the value of T% is the average transmittance of the band.

[0095] C Moisture content test: Test according to GBT 11417.7-2012, 4.5 method.

[0096] D. Surface hydrophilicity / wettability: The surface hydrophilicity of the contact lens is evaluated by WBUT (water film break up time). Procedure: Soak the contact lens in standard physiological saline overnight, grab one edge of the lens with tweezers and remove it from the water surface, and measure the time from the time the lens is removed from the water surface to the time the water film on the lens surface disappears (water film retention time). Determine the disappearance of the water film with the naked eye. Perform this measurement 3 times and calculate the average value.

[0097] E Contact Angle Test: The water contact angle (WCA) on a contact lens is a general measure of the surface wettability of a contact lens. The dynamic floating bubble contact angle of a contact lens is measured using an instrument from FDS Future Digital Sciences. The FDS equipment is capable of measuring advancing contact angles. The test is performed on sterilized finished lenses at room temperature.

[0098] The test results of the lenses obtained in Examples 3-9 are shown in Table 2.

[0099]

[0100] As can be seen from Table 1, in Examples 4-9 of the present invention, lenses with excellent performance can be obtained without improving the mold surface, and the obtained lenses have properties such as high oxygen permeability and high wettability surface. However, in Example 3, the macromolecular siloxane I of the present invention was not used, and the wettability was poor and the contact angle was large, indicating that the macromolecular siloxane I can significantly improve the hydrophilicity of the lens surface.

[0101] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.

Claims

1. A highly oxygen permeable silicone hydrogel contact lens, characterized in that: The invention comprises the following raw material components: macromolecular siloxane I, macromolecular siloxane II, small molecular siloxane, hydrophilic monomer, moisturizing agent, crosslinking agent, initiator and functional monomer; The molecular weight of the macromolecular siloxane I is 10000-15000, the molecular weight distribution coefficient is less than 1.8, and the structural formula is: Wherein, a:b:c=(0.1-0.2):0.1:(0.7-0.8); b / (a+c)=1 / 9, d is 7-8 or 23-30; The structural formula of the macromolecular siloxane II is: Wherein, R1 is H or CH3, R2 is one of C3-C6 alkyl groups, and n is a natural number between 9 and 24; The structural formula of the moisturizing agent is: Wherein, R is one of H, OH, and polyhydroxy compounds; X and Y are independently one of O, S, and N; and the anion may also be bromine, iodine, or other organic acid groups.

2. The highly oxygen permeable silicone hydrogel contact lens according to claim 1, characterized in that: The preparation method of the macromolecular siloxane I comprises the following steps: S1. Add 1,3-bis(3-chloropropyl)tetramethyldisilane, D3F, D3, D3H and phosphonium alkoxide into an organic solvent, add trifluoromethanesulfonic acid at low temperature to react, and post-treat to obtain intermediate I; S2, the intermediate I and allyl polyethylene glycol ether are subjected to addition reaction in an organic solvent, and post-processed to obtain intermediate II; S3, reacting the intermediate II with N-(3-dimethylaminopropyl)methacrylamide in an organic solvent, post-treating and freeze-drying to obtain the macromolecular siloxane I; The structural formulas of D3F, D3, D3H, phosphonium alkoxide, intermediate I and intermediate II are respectively: Among them, a:b:c=(0.1-0.2):0.1:(0.7-0.8); b / (a+c)=1 / 9, and d is 7 or 8.

3. The highly oxygen permeable silicone hydrogel contact lens according to claim 2, characterized in that: In S1, the temperature for adding trifluoromethanesulfonic acid is 0°C and the reaction temperature is 10°C; And / or, the post-treatment specifically comprises: using a mixed solvent of methanol and nitromethane in a volume ratio of 5:1 to extract oligomers and a small amount of un-ring-opened raw materials and other cyclic by-products generated in the reaction.

4. The highly oxygen permeable silicone hydrogel contact lens according to claim 2, wherein: In S2, the post-treatment is specifically as follows: dissolving the crude intermediate II in a mixed solvent of methyl tert-butyl ether and ethyl acetate in a volume ratio of 1:5, and then extracting the remaining raw material allyl polyethylene glycol ether with purified water.

5. The highly oxygen permeable silicone hydrogel contact lens according to claim 2, wherein: In S3, the post-treatment is specifically as follows: dissolving the crude macromolecular siloxane I in purified water, and then extracting with a mixed solvent of dichloromethane and ethyl acetate in a volume ratio of 1:1 to remove excess raw materials and other fat-soluble impurities.

6. The highly oxygen permeable silicone hydrogel contact lens according to claim 1, wherein: Calculated by mass percentage, the raw material components include: 30-40% of macromolecular siloxane I, 5-10% of macromolecular siloxane II, 10-20% of small molecular siloxane, 20-30% of hydrophilic monomer, 2-5% of moisturizing agent, 0.5-1.5% of crosslinking agent, 0.5-1% of initiator and 2-5% of functional monomer.

7. The highly oxygen permeable silicone hydrogel contact lens according to claim 1, wherein: The small molecule siloxane is methacryloxypropyl tris(trimethylsiloxy)silane and / or (3-methacryloxy-2-hydroxypropoxy)propyl bis(trimethylsiloxy)methyl; And / or, the hydrophilic monomer is one or more of N-vinyl pyrrolidone, N,N-dimethylacrylamide, N-methyl-N-vinylacetamide, and N-vinylacetamide; And / or, the cross-linking agent is ethylene glycol dimethacrylate and / or tetraethylene glycol dimethacrylate; And / or, the initiator is azobisisobutyronitrile; And / or, the functional monomer includes one or more of a UV absorber, a molecular weight regulator, a lens morphology improver, a demoulding accelerator, and a reactive dye.

8. The method for preparing a highly oxygen permeable silicone hydrogel contact lens according to any one of claims 1 to 7, characterized in that: The raw material components are mixed and dissolved in an organic solvent to obtain a polymer solution, and the polymer solution is placed in a mold for heat treatment under a protective atmosphere, and then naturally cooled and demolded and extracted to obtain the highly oxygen-permeable silicone hydrogel contact lens.

9. The method for preparing a highly oxygen permeable silicone hydrogel contact lens according to claim 8, characterized in that: The heat treatment is specifically as follows: keeping the temperature at 60° C. for 60-100 minutes, then increasing the temperature uniformly to 110-120° C. for 4 hours, and keeping the temperature for 1 hour.

10. The method for preparing a highly oxygen permeable silicone hydrogel contact lens according to claim 8, characterized in that: The demoulding and extraction are specifically to place the heat-treated mold in a 20wt%-80wt% ethanol aqueous solution for hydration, so as to demould the lens and extract a small amount of residual monomers and oligomers in the lens.

Citation Information

Patent Citations

  • Silicone hydrogel contact lens

    CN101163991A

  • Improved synthesis of cationic siloxane prepolymers

    CN101589091A

  • Method for applying coating onto silicone hydrogel lens

    CN104837612A

  • Sterically hindered hydroquinones as antifoulants for unsaturated monomers

    CN107532083A

  • Hydrophilic polysiloxane macromonomer, and production and use of the same

    CN101932632A

Cited By

  • A hydrogel composite defocus contact lens capable of synchronously correcting astigmatism and preventing myopia and a preparation method thereof

    CN122710392A

  • Contact lens compound, contact lens material composition, and contact lens

    CN122832294A